2019
DOI: 10.1177/1420326x19888572
|View full text |Cite
|
Sign up to set email alerts
|

Climatic clustering analysis for novel atlas mapping and bioclimatic design recommendations

Abstract: Defining and determining climatic zones accurately is crucial to inform the decision making of building designers and planners during early design phases of urban development. Characterizing the climatic zones allows estimation of energy requirements in buildings and develop climate adapted energy polices. Climatic zones can be defined by using the statistical cluster analysis. Data from weather stations can be used after standardization with zero mean and unit variance, to confirm that all variables are weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…The application of bioclimatic building design strategies for a sustainable built environment and urban planning requires an understanding of specific requirements of different climatic zones with respect to energy efficiency. 8,9 Such objectives also include the necessary efforts to address climate change. 9,10 Bioclimatic design strategies provide an efficient way to tap into the urban local climate and wind environment to provide optimum indoor comfort without the usage of mechanical systems.…”
Section: Introductionmentioning
confidence: 99%
“…The application of bioclimatic building design strategies for a sustainable built environment and urban planning requires an understanding of specific requirements of different climatic zones with respect to energy efficiency. 8,9 Such objectives also include the necessary efforts to address climate change. 9,10 Bioclimatic design strategies provide an efficient way to tap into the urban local climate and wind environment to provide optimum indoor comfort without the usage of mechanical systems.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 reports the values of optimal WWR upon varying the orientation of the office building's two main facades. Iran's territory is divided into four diverse climates [64]: (i) mild and wet, in the north of Iran (near the Caspian Sea), (ii) hot and dry, mainly in the central regions, (iii) cold and dry, in the high mountains, (especially in the north-west), and (iv) hot and wet, in the southern regions (near the Persian Gulf and the Gulf of Oman), as reported in Figure 2.…”
Section: Building Modelingmentioning
confidence: 99%
“…Four cities in four different Iranian climatic zones [64,65] were considered in this study, as indicated below. Iran's territory is divided into four diverse climates [64]: (i) mild and wet, in the north of Iran (near the Caspian Sea), (ii) hot and dry, mainly in the central regions, (iii) cold and dry, in the high mountains, (especially in the north-west), and (iv) hot and wet, in the southern regions (near the Persian Gulf and the Gulf of Oman), as reported in Figure 2. Four cities in four different Iranian climatic zones [64,65] were considered in this study, as indicated below.…”
Section: Building Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Construction details, according to (Table 1) was applied for the modeled building. In this climate, if the amount of solar absorption coefficient is lowered, the thermal performance of the facade will improve [77]. So that the facade of fire brick with the lowest solar absorption coefficient, about 0.35, is the most suitable facade [78] and wooden doors and wooden window frames in the building [69] are the best option for this type of climate.…”
Section: Details Of Building Modelingmentioning
confidence: 99%